A prospective study on placental migration in mid trimester low lying placenta - Char, Debasish; Biswas, Sucheta; Das, Swapan; Mandal, Priyadarshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Objectives of the study were: to assess migration of low-lying placenta diagnosed by ultrasound around 20 weeks of gestation and to evaluate the factors influencing placental migration as well as to reduce feto-maternal morbidity and or mortality by excluding placenta previa and placenta accreta early. Methods: All antenatal mothers undergoing routine transabdominal congenital anomaly scan around 20 weeks of gestation were subjected to transvaginal ultrasonography to confirm low lying placenta. Every 4 weekly transvaginal ultrasonography was repeated until the lower edge of placenta migrated beyond 3 cm of internal cervical os or the patient had delivered, which one was earlier. Results: Out of total 686 cases, only 56 (8.16%) mothers had low-lying placenta in mid trimester. Follow up of these 56 cases showed that 33 (58.93%) cases placenta had migrated at term and 23 (3.35%) cases persist as placenta previa. The rate of migration of placenta was 80.76%, 39.13% and 42.86% in mothers following previous vaginal delivery, caesarean section or prior history of MTP/suction and evacuation. Placental migration was 80% and 47.39% where the distance between the internal cervical os and lower edge of placenta was between 2.1-3 cm and between 1.5-2 cm respectively. No placental migration was noted where the initial distance was less than 1.5 cm. Placental migration was more common in anteriorly situated placenta (65.85%) than the posterior one (40%). Conclusions: The rate of placental migration at term was 58.93%. However, factors like previous caesarean section, previous history of MTP or suction and evacuation, posteriorly situated placenta and placenta lying 1.5 cm from the internal cervical os may interfere with placental migration.